Tafsir Identitas dan Kekerasan Keagamaan - Abdul Munir Mulkhan (Universitas Islam Indonesia, 2002)
The article below traces the fundamentalism either with violence or without radicalization is not only phenomenon that emerges from the religion community but also rises from secular community. The fundamentalism of religion denotes general phenomena, which appears from the practices of religions as well as the fundamentalism of secularism and modernism. In this case, the position of human pertaining to The Holy Scripture shows sociological dimension according to an interpretation. In the history of Islam and the great religions in the world, fundamental ism either radical or not radical constitutes a social phenomena reacting to social change. The dysfunction of the values of the religion doctrine that becomes the reference of social conduct motivates the member of the community carries out to reject every social change by isolating themselves from the change. While the appearance of reinterpretation toward the old doctrine of religion faces the social change.